Identification and quantitative analysis of oligosaccharides in wheat flour using LC–MS. (May 2015) - Liu, Zhiqian; Rochfort, Simone
Abstract: Considered as dietary fibres with properties of prebiotics, fructo-oligosaccharides have great potential to be used as food additives to promote human health. Accurate quantification of such compounds in food crops is thus an important step in evaluating and developing designer food products. Here we describe the development and validation of a liquid chromatography–mass spectrometry (LC–MS) based method for accurate quantification of three major tri-saccharides (1-kestose, 6G-kestose and raffinose) in wheat flour. The tri-saccharides were extracted from flour using hot water, separated with a Prevail Carbohydrate ES column and quantified by a Q-TOF mass spectrometer. The validated method was applied to a large number of random flour samples, allowing us to define the natural variation of each tri-saccharide and to reveal a clear correlation ( R 2  = 0.69, P  < 0.001) between 6G-kestose and total fructan content in wheat flour. Highlights: A robust, sensitive method for quantitation of trisaccharides in wheat flour is presented. Identification of key oligosaccharides by LC–MS is presented. LOD, LOQ and linearity are presented and demonstrated in 20 different wheat lines.